1996
DOI: 10.1080/00071669608417883
|View full text |Cite
|
Sign up to set email alerts
|

Use of four types of litter for rearing broilers

Abstract: 1. One hundred and forty four Shaver broiler chicks (Starbro 15) were reared from 4 d to 56 d of age on 4 types of litter: sawdust, paddy straw, sand and rice husk each spread to a depth of 75 mm. 2. Birds reared on rice husk litter showed the greatest food consumption, greatest weight gain, best food conversion efficiency and scored highest in production number. 3. Survivability was also highest with rice husk group (94.4%) but differences in this variable were not thought to be attributable to types of litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 2 publications
2
8
0
1
Order By: Relevance
“…However, result of present study is alike with the result of Malone et al (1982) and Anisuzzaman and Chowdhury (1996). Malone et al (1982) reported a significantly higher body weight when maintained on shredded paper than saw dust, and Anisuzzaman and Chowdhury (1996) noticed significantly higher body weight in birds those were maintained on rice husk as compared to other litter materials used.…”
Section: Discussionsupporting
confidence: 72%
“…However, result of present study is alike with the result of Malone et al (1982) and Anisuzzaman and Chowdhury (1996). Malone et al (1982) reported a significantly higher body weight when maintained on shredded paper than saw dust, and Anisuzzaman and Chowdhury (1996) noticed significantly higher body weight in birds those were maintained on rice husk as compared to other litter materials used.…”
Section: Discussionsupporting
confidence: 72%
“…In the same line, Bilgili et al (2009) found that bedding materials (pine shavings, pine bark, chipped pine, mortar sand, ground hardwood pallets, chopped straw, ground door filler, and cotton-gin trash) had little influence on the live performance of broilers. On the other hand, bedding type was found to significantly affect growth performance of broilers (Malone et al, 1982 andDemirulus et al, 1998;Bilgili et al, 1999a;Bilgili et al, 1999b;Anisuzzaman and Chowdhury, 1996;Al-Homidan and Robertson, 2007;Grimes et al, 2007;Huang et al, 2009;Torok et al, 2009 andAtencio et al, 2010). Moreover, Grimes et al, (2006) showed that growth performance might be negatively affected by caking over of litter.…”
Section: Body Weight (Bw) and Body Weight Gain (Bwg)mentioning
confidence: 99%
“…A few studies focused on sand as a bedding material, indicating that it supported adequate performance criteria (Bilgili et al, 1999a,b;Bowers et al, 2003;Miles and Chamblee, 2003). However, a study in southeast Asia found that sand and paddy straw did not support production parameters when compared with sawdust and rice husks (Anisuzzaman and Chowdhury, 1996).…”
Section: Introductionmentioning
confidence: 98%